Deacetylation of per-acetatylated glycopyranosides: an overall pattern for acidic catalyzis; Chemical Physics Letters; Vol. 723 - Nasibullin R. T. Rinat Talgatovich; Valiev R. R. Rashid Rinatovich; Fayskanova K. M. Kseniya Mikhaylovna; Stepanova E. V. Elena Vladimirovna; Cherepanov V. N. Viktor Nikolaevich; Filimonov V. D. Viktor Dmitrievich; Sundholm D. Dage (2019, 2019)
Title screen